2017
DOI: 10.1186/s13690-017-0193-9
|View full text |Cite
|
Sign up to set email alerts
|

Individual and community level factors with a significant role in determining child height-for-age Z score in East Gojjam Zone, Amhara Regional State, Ethiopia: a multilevel analysis

Abstract: BackgroundIn Ethiopia, child undernutrition remains to be a major public health challenge and a contributing factor for child mortality and morbidity. To reduce the problem, it is apparent to identify determinants of child undernutrition in specific contexts to deliver appropriately, targeted, effective and sustainable interventions.MethodsAn agroecosystem linked cross-sectional survey was conducted in 3108 children aged 6–59 months. Multistage cluster sampling technique was used to select study participants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 43 publications
(53 reference statements)
10
15
1
Order By: Relevance
“…The pooled odds ratio of women who gave birth at their home was increased by five folds as compared to those who gave birth at health facilities. This finding is in agreement with a multilevel study in twenty-two Sub Saharan Africa including Ethiopia [ 6 ], and another multilevel study conducted in Ethiopia [ 24 ]. This is due to the fact that home delivery in Ethiopia is usually attended by traditional birth attendants who do not have the knowledge on the benefits of optimum breastfeeding and the harms following prelacteal feeding.…”
Section: Discussionsupporting
confidence: 92%
“…The pooled odds ratio of women who gave birth at their home was increased by five folds as compared to those who gave birth at health facilities. This finding is in agreement with a multilevel study in twenty-two Sub Saharan Africa including Ethiopia [ 6 ], and another multilevel study conducted in Ethiopia [ 24 ]. This is due to the fact that home delivery in Ethiopia is usually attended by traditional birth attendants who do not have the knowledge on the benefits of optimum breastfeeding and the harms following prelacteal feeding.…”
Section: Discussionsupporting
confidence: 92%
“…Obviously, poverty and economic inequality hinder the financial ability for household food access, inadequate sanitation, and health care utilization, which are the major contributing factors for the development of malnutrition including stunting [34]. In contrary, household wealth had no significant association with stunting in study conducted in East Gojjam, Ethiopia [35]. Appropriate infant and young child feeding has been identified as one of key determinants of child under nutrition particularly stunting [10].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a lack of privacy and security were related to women emptying bags and buckets at night, a behavior that can often increase the exposure of women to the threat of violence or sexual assault (Winter et al, 2019). Generally, studies that compared access to sanitation between men and women found largely unremarkable gender differences (Ugbomoiko et al, 2009;Al-Delaimy et al, 2014;Alemu et al, 2017;Baker et al, 2018). However, one study in rural Ethiopia found that male-headed households were ∼4-fold more likely to use household latrines than female-headed families (Aiemjoy et al, 2017).…”
Section: (Continued)mentioning
confidence: 99%
“…Kwiringira et al, 2014;Sato et al, 2016;Khan et al, 2017;Aluko et al, 2018;Angoua et al, 2018;Budhathoki et al, 2018;Dendup et al, 2018;Desalegn et al, 2018;Lubon et al, 2018;Winter et al, 2019 Gender differences in accessing a latrine were largely unremarkable. Ugbomoiko et al, 2009;Al-Delaimy et al, 2014;Alemu et al, 2017;Baker et al, 2018 Women and girls were burdened by latrines which lacked privacy and security. Kwiringira et al, 2014;O'Reilly and Louis, 2014;Winter et al, 2019 Male-headed households were more likely to have a household latrine.…”
Section: Both Infrastructural and Educational Interventions Are Succementioning
confidence: 99%